Konstruksi Motivasi Internal dalam Menghafal Al-Qur'an pada Peserta Program Tahfidz Madrasah Aliyah Unggulan KH. Abd. Wahab Hasbullah Tambakberas Jombang - Munasofah; Wafiyul Ahdi; Alaika M. Bagus Kurnia Ps (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This study aims to analyze the construction of internal motivation in memorizing the Qur'an among students participating in the Tahfidz Program at Madrasah Aliyah Unggulan KH. Abd. Wahab Hasbullah, Tambakberas, Jombang. A qualitative approach with a phenomenological design was employed to explore the participants' lived experiences in developing their motivation for Qur'an memorization throughout the Tahfidz program. Data were collected through in-depth interviews, observations, and documentation involving Tahfidz students, the program coordinator, and Qur'an teachers as research participants. Data were analyzed interactively using the Miles, Huberman, and Saldaña model, encompassing data condensation, data display, and conclusion drawing and verification. The findings reveal that internal motivation is constructed through four interrelated dimensions: a conducive learning environment, perseverance in coping with academic demands, future orientation, and an intrinsic need to continuously engage with the Qur'an. These dimensions are fostered through a structured Tahfidz program characterized by continuous mentoring, reflective evaluation, and the habituation of Qur'anic practices. The study concludes that the effectiveness of Tahfidz education depends not only on memorization methods but also on the institution's capacity to establish a supportive learning ecosystem that sustains students' internal motivation and enhances the overall quality of Tahfidz education. Keywords : Qur'an Memorization; Internal Motivation; Tahfidz Program